Response of guava (Psidium guajava) genotypes to air-layering under sub-humid southern Rajasthan - Chand, G; Singh, V; Sarolia, D K; Singh, D K (Current Horticulture, 2025)
The evaluation of the genotypes guava (Psidium guajava L.) for air layering under sub humid southern plains of Rajasthan conditions was done from 5 to 15 July 2015-16. The genotypes, L-49, Allahabad Safeda, Lalit, Red Fleshed, Pant Prabhat, Safed Jam, Arka Amulya, Arka Mridula, MPUAT S-1, MPUAT S-2, Shweta, Burfkhan, Sarbati, RCGH.-1 and One-Kg were used. Among the genotypes, early root initiation, percentage of rooted air layers, survival percentage and vigour index were maximum in Lalit, while and the number of secondary roots were highest in L- 49 and root: shoot ratio in Shweta. Poor response to rooting was observed in One-Kg.